(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Gout is a severe form of arthritis caused by a buildup of uric acid crystals in the joints. One of the most common types of arthritis, it can occasionally cause excruciating pain that causes immobility. Although it can affect other joints such as the ankles, knees, wrists, and fingers, gout typically affects extremity joints, particularly the big toe. Gout is distinguished by sudden, severe joint pain, redness, edema, and inflammation; the affected area is frequently warm to the touch. Gout attacks are excruciatingly painful and can last from a few days to several weeks. They may worsen again if nothing is done. Acid uric is a waste product that is created naturally during the breakdown of purines; the kidneys typically remove it from the body. Uric acid builds up in the blood in gout patients because their bodies either create too much of it or their kidneys are unable to properly remove it from their bodies. Elevated uric acid can crystallize and accumulate in soft tissues and joints, causing the typical goutrelated inflammatory reaction. Gout can be caused by a variety of factors, including heredity, obesity, a poor diet, and specific medical conditions. Gout is treated and managed with a combination of dietary changes, lifestyle changes, anti-inflammatories, and uric acid-lowering medications. Gout can be avoided by maintaining a healthy weight, avoiding purine-rich foods, drinking plenty of water, and limiting alcohol consumption.